Multi-criteria model for selecting project managers in the public sector. (25th August 2022) - Escobar, Fernando; Varajão, João; Takagi, Nilton; Neto, Ulysses Almeida
To assure effectiveness in the management of projects, it is required that project managers have the right competencies, according to the context and characteristics of each project they are involved. Based on several competencies frameworks (including PMI's PMCDF, IPMA's ICB, APM's CF, and AIPM's PCSPM), this paper proposes a unified multi-criteria model to be used as a decision-making tool for selecting the most suitable managers and defining competencies pathways for public sector projects. A hierarchical structure comprising weighted elements related to behavioural, management, and contextual/organisational competencies is proposed. For researchers, the presented model of competencies enables a better understanding of the phenomenon and can be used to structure further research in other contexts than the public sector. It is also a valuable tool for practitioners and project management offices since it allows comparing the candidates for managing a project using an organised and rigorous process anchored on empirically well-grounded criteria.